PEMANFAATAN PLATFORM MERDEKA MENGAJAR DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR ISLAM TERPADU ASY-SYIFA KOTA JAMBI - Laelia, Bheta Adi; Kiki Fatmawati (Al-mujahidah, 2025)
The implementation of the Merdeka Curriculum requires innovation in the learning process, one of which is through the Merdeka Teaching Platform (PMM). However, in practice, there are still obstacles, such as the lack of teacher training on the features in PMM, so that not all PMM features can be utilized properly. In addition, the lack of skills in using technology is also a problem in utilizing PMM. This study aims to describe the utilization of Merdeka Mengajar Platform in implementing the Merdeka Curriculum at Asy-Syifa Integrated Islamic Elementary School (SDIT) in Jambi City, identify obstacles and formulate solutions implemented by the school. The research method used is a case study with a qualitative approach. Data is collected through observation, interviews, and documentation analysis. The subjects in this study are the principal, deputy head of curriculum and homeroom teacher V.A who has utilized the Merdeka Mengajar Platform. Data analysis uses the stages of data reduction, data presentation, and conclusion drawing. The results showed that PMM was utilized diversely according to the needs of teachers at SDIT Asy-Syifa Jambi City, ranging from accessing learning modules, participating in independent training, to sharing good practices. The main obstacles faced include limited internet access, time constraints, lack of comprehensive training, and teacher adaptation to PMM features that still require improvement. As a solution, the school has made several efforts, such as providing additional internet access and forming a learning community for teachers. This study concludes that despite the obstacles, PMM makes a positive contribution to the implementation of Merdeka Curriculum at SDIT Asy-Syifa Jambi City, and there needs to be continuous support from various parties to maximize its utilization. Key Word : Independent Teaching Platform, Independent Curriculum, Integrated Islamic Elementary School.